Justification of the method for determining the dynamic parameters of the mobile fire fighting installation operator - Abramov, Yuriy; Basmanov, Oleksii; Sobyna, Vitaliy; Kovalov, Oleksandr; Feshchenko, Andrey (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is the process of functioning of the "man-robot" system. The task to coordinate parameters of the human operator and the robot is investigated. Aligning these parameters is based on the method of determining the dynamic parameters of the human operator using mathematical models that describe two types of relative errors. The first type includes relative errors in determining the dynamic parameters of the operator, which depend on the error in determining the signals characterizing his response to the test impact. The second type of relative errors is the methodical error, which is due to the approximation of partial derivatives. The formation of a test impact on the operator is carried out using an interactive whiteboard. The method is based on finding the roots of a linear system of algebraic equations, for the construction of which an approximation of partial derivatives from signals characterizing the operator's response to the test effect is used. The parameters of this system of algebraic equations depend on time parameters. Determination of time parameters is carried out using tolerance criteria and using nomograms. When justifying the main parameter of the test impact on the operator – the speed of movement of the fire front on the interactive whiteboard screen, the properties of the angular eye control system of the mobile fire installation operator are used. These properties are formalized as a mathematical model of dynamic error, which occurs in the process of tracking by the operator the image of a fire on the interactive whiteboard screen. To verify the obtained results, a test problem has been solved; it is shown that the error in determining the dynamic parameters of the operator does not exceed 1.0 %. The results reported here could be used for designing mobile fire installations of a new generation, the structure of which is based on the use of segways